Analysis of Partial Edentulism Of Kennedy’s Class I Classification Based on Gender and Arch- A Retrospective study - RASIDI, MOHAMAD QULAM ZAKI BIN MOHAMAD; PANDURANGAN, KIRAN KUMAR; PRABU, DINESH (The journal of contemporary issues in business and government, 2021)
A partially edentulous arches classification helps in identifying the teeth combinations, better communication and planning a good treatment. Kennedy’s classification will provide immediate prosthesis support recognition, visualization of risk, and design assessment that needed for a partial denture that will be fabricated. Therefore, this purpose of this study is to evaluate the partial edentulism of Kennedy’s Class I based on gender and arch. An institution based retrospective study was conducted among partial edentulism patients who visited Private Dental Hospital, Chennai. Data collection was obtained by reviewing 86,000 patients records between June 2019 and March 2020. The study was done in 103 patients among gender and arch by doing clinical examination for evaluating the partial edentulism of Kennedy’s Class I. The data were collected and tabulated in excel sheets which were imported to SPSS version 20. Descriptive statistics and Chi-square test were used to determine the correlation between the variables. In this present study, out of 103 patients, partial edentulism of Kennedy’s Class I is more common in males(56%) than females and the most common arch was found to be mandibular arch (52%). This study result concludes that there is no association between the gender and arches for patients with Kennedy’s Class I partial edentulism (p>0.05).